Pengembangan Media Pembelajaran Biologi Berbasis Video Animamsi Stop-Motion sebagai Sumber Belajar SISWA SMA/MA - Ananda Putri, Ananda Putri Ananda Putri; Nur, Fadilla Annisa; Sari, Nabila Syahna Permata; Nurliana, Maulidya; Rahayu, Reni; Daulay, Rabiah Afifah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this development and research is to ascertain whether Stop Motion video learning media can be used to prohibit biological material about the human circulatory system. Media and materials experts have evaluated this idea. The ADDIE model is the development model used in this study. Class XI high school students were used as research subjects. The instrument used was a student response questionnaire. Based on the data analysis method: Validation of expert lecturers on the feasibility of the Stop Motion video received a score of 4.0 in the good category, and the reliability test showed an approval proportion of 85.3% (reliable). While the reliability test showed the proportion of agreement was 80.1% (reliable), the results of the Stop Motion video feasibility validation got a score of 3.9 in the good category. It can be concluded that making Stop Motion videos about the circulatory system in humans is very possible and can be used as an alternative method of learning biology. Keywords: learning media, stop motion video, circulatory system in humans